2000
DOI: 10.1038/sj.ijo.0801185
|View full text |Cite
|
Sign up to set email alerts
|

Similar weight loss with low-energy food combining or balanced diets

Abstract: OBJECTIVE: The goal of this study was to evaluate the effect of two diets (`food combining' or dissociated vs balanced) on body weight and metabolic parameters during a 6-week period in an in-hospital setting. SUBJECTS AND DESIGN: 54 obese patients were randomly assigned to receive diets containing 4.5 MJaday (1100 kcaladay) composed of either 25% protein, 47% carbohydrates and 25% lipids (dissociated diet) or 25% protein, 42% carbohydrates and 31% lipids (balanced diet). Consequently, the two diets were equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
(12 reference statements)
1
15
0
Order By: Relevance
“…Fourteen randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate to fat on systolic and diastolic blood pressure, all of which were included in the meta-analysis (Golay et al, 2000;Foster et al, 2003;Lovejoy et al, 2003;Clifton et al, 2004;Ley et al, 2004;Dansinger et al, 2005;Ebbeling et al, 2005;Howard et al, 2006b;Ebbeling et al, 2007;Gardner et al, 2007;Maki et al, 2007b;Phillips et al, 2008;Frisch et al, 2009;Sacks et al, 2009). Six trials were subsequently identified in the update search Gulseth et al, 2010;Jebb et al, 2010;Howard et al, 2010;Tierney et al, 2011;Brooking et al, 2012) (Cardio-metabolic review, incident hypertension and blood pressure chapter p 49, 53; Update search table 47).…”
Section: Vascular Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourteen randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate to fat on systolic and diastolic blood pressure, all of which were included in the meta-analysis (Golay et al, 2000;Foster et al, 2003;Lovejoy et al, 2003;Clifton et al, 2004;Ley et al, 2004;Dansinger et al, 2005;Ebbeling et al, 2005;Howard et al, 2006b;Ebbeling et al, 2007;Gardner et al, 2007;Maki et al, 2007b;Phillips et al, 2008;Frisch et al, 2009;Sacks et al, 2009). Six trials were subsequently identified in the update search Gulseth et al, 2010;Jebb et al, 2010;Howard et al, 2010;Tierney et al, 2011;Brooking et al, 2012) (Cardio-metabolic review, incident hypertension and blood pressure chapter p 49, 53; Update search table 47).…”
Section: Vascular Functionmentioning
confidence: 99%
“…Nineteen randomised controlled trials that presented evidence on diets differing in the proportion of carbohydrate to fat on fasting total cholesterol were included in the metaanalysis (Campos et al, 1995;Nelson et al, 1995;Ginsberg et al, 1998;Turley et al, 1998;Zambon et al, 1999;Golay et al, 2000;Colette et al, 2003;Couture et al, 2003;Lovejoy et al, 2003;Clifton et al, 2004;Ley et al, 2004;Pelkman et al, 2004;SegalIsaacson et al, 2004;Cornier et al, 2005;Lofgren et al, 2005;Petersen et al, 2006;Howard et al, 2006b;Due et al, 2008b;Frisch et al, 2009). Five trials were subsequently identified in the update search Howard et al, 2010;Haufe et al, 2011;Tierney et al, 2011;Brooking et al, 2012) (Cardio-metabolic review, the hyperlipidaemias and blood lipids chapter p 65-72; Update search table 62).…”
Section: 30mentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid weight loss on these diets is attributed to high amounts of water loss (60 to 70% of weight loss was water) and the dieters often regain weight rapidly once normal eating is resumed (Andersen, Backer, Stokholm, & Quaade, 1984;Wadden & Stunkard, 1986). However, it is important to reemphasize that energy intake, not energy consumption or distribution of calories, determines weight loss (Golay et al, 2000). Therefore, a balanced diet that provides a reduced intake of calories is preferable as the approach helps children achieve long-term weight control with healthier eating behaviors.…”
Section: Very Low Calorie Diets and Low Carbohydrate Dietsmentioning
confidence: 99%